Real-Time Defects Analyses Using High-Speed Imaging during Aluminum Magnesium Alloy Laser Welding - Sabin Mihai; Diana Chioibasu; Muhammad Arif Mahmood; Liviu Duta; Marc Leparoux; Andrei C. Popescu (Metals, 2021)
In this study a continuous wave Ytterbium-doped Yttrium Aluminum Garnet (Yb: YAG) disk laser has been used for welding of AlMg3 casted alloy. A high-speed imaging camera has been employed to record hot vapor plume features during the process. The purpose was to identify a mechanism of pores detection in real-time based on correlations between metallographic analyses and area/intensity of the hot vapor in various locations of the samples. The pores formation and especially the position of these pores had to be kept under control in order to weld thick samples. Based on the characterization of the hot vapor, it has been found that the increase of the vapor area that exceeded a threshold value (18.5 ± 1 mm2) was a sign of pores formation within the weld seam. For identification of the pores’ locations during welding, the monitored element was the hot vapor intensity. The hot vapor core spots having a grayscale level reaching 255 was associated with the formation of a local pore. These findings have been devised based on correlation between pores placement in welds cross-section microscopy images and the hot vapor plume features in those respective positions.